Promotion of Small Scale Industries for District Development: the Case of Atwima District - Fekadu, Terefe Dama (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Development Planning and Management,